Implementasi Kebijakan Percepatan Penurunan Stunting di Provinsi Jawa Tengah (Pelaksanaan Perpres Nomor 72 Tahun 2021) - Kurnia Lintang Larasati; Bambang Budi Raharjo (Pusat Riset dan Inovasi Nasional, 2025)
Central Java Province targets a 16% reduction in stunting by 2023, with the prevalence having been reduced from 31.2% in 2018(Riskesdas, 2018) to 20.8% in 2022 (SSGI). The causes of stunting in Central Java include a lack of knowledge about balanced nutrition, proper parenting, and lack of access to proper drinking water and sanitation. This study aims to determine the implementation of the Central Java Provincial Health Office strategy in reducing stunting rates. The study used a qualitative design with descriptive methods and in-depth interviews, involving samples from the Health Office, TP-PKK, and Head of Puskesmas through snowball sampling techniques. The results showed that implementation at the Puskesmas level has not been optimal, with low community participation. Semarang City has many stunting reduction programs, in contrast to Brebes Regency. The overall provincial target has been achieved, but operational funding constraints hinder optimal program implementation.